Comparative Analysis of Postoperative Radiotherapy Dose Escalation in Oral Cavity Cancer Patients with Positive Margins: A Propensity Score-Matched Study - Sarawagi, Rashmi; Padmanabhan, Aravind; Prajapati, Raju; Gupta, Manish; Das, Saikat; Kharade, Vipin; Tiwari, Arnav; Reddy, B. Srinivas; Shrivastava, Neelesh; Pasricha, Rajesh (South Asian Journal of Cancer, 2025)
Introduction This study aimed to determine the impact of postoperative (PO) radiotherapy (RT) dose escalation in oral cavity squamous cell carcinoma (OCSCC) patients with positive margin (PM) in terms of local control (LC), duration of RT interruption, and toxicity in a tertiary care center.Materials and Methods Patients with OCSCC who were candidates for adjuvant RT were categorized into PM and negative margin (NM) arms depending on the margin status as per the histopathology report retrospectively. PM and NM patients received a total dose of 66 Gy to the site of the PM and 60 Gy for the NM. LC, acute and chronic toxicities, and duration of RT interruption were evaluated.Results A total of 56 patients were included in the study, of whom 39 had NM and 17 had PM. After propensity score matching, 11 patients were matched in each arm. The mean duration of RT treatment in the PM and NM arms were 49.5 days (standard deviation [SD] = 5.4) and 50.7 days (SD = 10.15) (p = 0.3), with mean interruptions of 3.9 days (SD = 3.9) and 3.8 days (SD = 6.2), respectively (p = 0.39). LC was 72.7% in the PM arm and 81.8% in the NM arm (p = 0.6). Acute and chronic toxicities were comparable between the two arms.Conclusion Dose escalation to 66 Gy for PM during adjuvant RT for PO OCSCC can be used as an alternative strategy to reresection, especially in patients who have poor performance status, who have negative consent for surgery, and who have more than one adverse prognostic factor with comparable LC and toxicity as in the NM. However, further prospective studies are needed to establish its role as an alternative, which is highly unlikely in modern oncology practice, as PM patients are rarely seen in clinics currently with good surgical oncology practices.
Keywords: oral cavity squamous cell carcinoma; radiotherapy; positive margin; negative margin; postoperative